TO THE QUESTION OF PSYCHOLOGICAL CULTURE DEVELOPMENT OF DOCTORS IN THE SYSTEM OF ADDITIONAL EDUCATION - L. V. Skorova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The article describes the importance of psychological culture of the doctors professional activity. It presents the results of the pilot research of doctors psychological culture and the experience of its development in the additional education system by the programs of advanced training and professional retraining of doctors. Also a paper provides the basic work strategy with doctors to develop their psychological culture.